Good leadership practices in contexts of unpredictability - Roque, H.C.; Ramos, M. (Handbook of research on reinventing economies and organizations following a global health crisis, 2021)
COVID-19 was declared the pandemic on 11 March 2020, and the world is still in the throes of an unprecedented and highly unpredictable public health crisis, with consequences at an individual, group, organisational, and societal level. Under such dire circumstances, leadership is of decisive importance, as the repercussions of the decisions taken may, now more than ever, be crucial. Hence, leadership is currently essential not only for the success, but for the actual survival of organisations. In a scenario of ongoing change with unforeseeable outcomes, the absence of good leadership could mean the demise of an organisation. Grounded on the theory of responsible leadership and the theory of shared leadership, the authors present the good leadership practices that are considered essential during times of major unpredictability such those currently underway.